Tumor‐Targeting Salmonella typhimurium A1‐R Sensitizes Melanoma With a BRAF‐V600E Mutation to Vemurafenib in a Patient‐Derived Orthotopic Xenograft (PDOX) Nude Mouse Model. Issue 8 (25th April 2017) - Kawaguchi, Kei; Igarashi, Kentaro; Murakami, Takashi; Zhao, Ming; Zhang, Yong; Chmielowski, Bartosz; Kiyuna, Tasuku; Nelson, Scott D.; Russell, Tara A.; Dry, Sarah M.; Li, Yunfeng; Unno, Michiaki; et al.
ABSTRACT: Previously, a BRAF‐V600E‐mutant melanoma obtained from the right chest wall of a patient was grown orthotopically in the right chest wall of nude mice to establish a patient‐derived orthotopic xenograft (PDOX) model. Trametinib (TRA), an MEK inhibitor, caused tumor regression. In contrast, another MEK inhibitor, cobimetinib (COB) could slow but not arrest growth or cause regression of the melanoma PDOX. First‐line therapy temozolomide (TEM) could slow but not arrest tumor growth or cause regression. In addition, vemurafenib (VEM) was not effective even though VEM is supposed to target the BRAF‐V600E mutation. We also previously demonstrated that tumor‐targeting with S. typhimurium A1‐R combined with TEM was significantly more effective than either S. typhimurium A1‐R alone or TEM alone on the melanoma PDOX with the BRAF‐V600E mutation. The present study used this PDOX model of melanoma to test its sensitivity to VEM combined with S. typhimurium A1‐R compared to VEM alone and VEM combined with COB. VEM combined with S. typhimurium A1‐R was significantly more effective than VEM alone or VEM combined with COB ( P = 0.0216) which is currently first line therapy for advanced melanoma with a BRAF‐V600E mutation. J. Cell. Biochem. 118: 2314–2319, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Salmonella typhimurium A1‐R‐GFP targeting the melanoma PDOX. Left: Brightfield image of melanoma. Right: Fluorescence image of Salmonella typhimurium A1‐R‐GFP that has targeted the melanoma PDOX.